A coupled SPH–FVM method for simulating incompressible interfacial flows with large density difference. (1st July 2021) - Xu, Yixiang; Yang, Gang; Zhu, Yawei; Hu, Dean
Abstract: The coupling of smoothed particle hydrodynamics (SPH) with the finite volume method (FVM) is presented for simulation of incompressible interfacial flows with large density difference. The flow phase with small volume ratio is expressed by SPH particles and the other phase is defined on the stationary FVM grids. In the present SPH–FVM coupling algorithm, the dynamic interface is tracked by the movement and distribution of SPH particles. The flow field is solved by FVM grids. The coupling framework is established through a smooth transition between the SPH particles and the FVM grids in the overlapping regions. The continuum surface force model is brought into the coupling algorithm to evaluate the effect of surface tension. A mixed pressure Poisson equation (PPE) source term is taken to ensure the incompressibility of the fluid represented by the SPH particles. The moving interfaces can be reproduced accurately and conveniently by the SPH–FVM coupling algorithm. Several benchmark numerical problems of incompressible interfacial flows with large density difference are investigated to demonstrate the accuracy and applicability of the SPH–FVM coupling method.